Dinamika Hubungan Sosial-Keagamaan pada Masyarakat Nelayan di Karangantu Banten - Yanwar Pribadi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2017)
This paper explores the dynamics of socio-religious interactions among the inter-ethnic fishermen community in the former seaport of the Sultanate of Banten, i.e. in the Karangantu Port, Serang, Banten. The study focuses on the socio-religious interactions between migrants and local residents, and among the migrants themselves. This paper more broadly investigates the government’s policies on marine and fisheries sectors since 2000. Main issues discussed are the background of the history of Banten as the center of maritime power; the arrival and interaction between foreign and Nusantara traders and fishermen and local people; decentralization policies; patterns and forms of the inter-ethnic interactions; and the influence of decentral-ization policies towards the development of Banten’s maritime world. This paper uses ethnographical and historical approaches. The author argues that the inter-ethnic interactions in the Banten north coast area are socio-economic-cultural interactions that have long been intertwined and can be regarded as ideal multiculturalism interactions on the one hand. However, the policies of the central and regional government in marine and fisheries sectors have not generated the right solution to improve and empower Banten’s fishermen community, as it did occur in the 16th and 17th centuries.